Essays on the Role of Investment Banks as IPO Underwriters, Mutual Fund Managers, and Merger Advisors - (:unkn) unknown (My University, 2013)
In my first essay, I examine whether the focus on advisors' merger completion abilities is driven by acquirers seeking to complete mergers unconditionally, regardless of value implications, or if it is driven by value-maximization considerations. Advisors that complete a higher percentage of announced mergers are associated with more certain future merger completion. Results reveal that completion expertise has positive value implications, but only for acquirers with strong corporate governance. Results also suggest that the level of corporate governance of the acquirer determines the value consequences of an advisor's merger completion expertise. In my second essay, I examine the way investment banks allocate IPOs to their affiliated mutual funds worldwide. I analyze IPO allocations to affiliates globally and find significant cross-country differences in the first-day returns of these IPOs. I find some support for the dumping ground hypothesis outside the U.S. In addition, IPO allocations to all mutual funds--both affiliated and unaffiliated--in countries with strong investor protection tend to have higher first-day returns, benefiting fund investors. Overall, the evidence suggests the presence of an economically significant conflict of interest within financial conglomerates for which prior literature has not found robust empirical support.